One two ten - an experiment in theatre and film - Leong, Li Qing (Nanyang Technological University, 2022)
The following is a report detailing and documenting my process creating a devised theatre production, one two ten over the course of a semester. This piece came from a place of confusion, frustration, and desire for catharsis. In short, it was a letter of reminder to me and others – confront the issues you are running from or risk going in circles. one two ten was a 20-minute stage performance with some film elements. It delves into the inner mind of GIRL, who recently went through a traumatic event. Within her mind, she hears VOICE, who constantly presses her to ask about her day and alluding to the events of the traumatic night. GIRL on the other hand, continues to avoid answering questions, changing the subject, and getting increasingly frustrated. Finally in an attempt to break away from VOICE, she attempts to leave but is pulled back, creating a roundabout situation that repeats itself over and over again.